Privacy and the news media - Frost, Chris 1950- (Routledge, 2020)
"Critically examining current journalistic practices using both theoretical and applied approaches, this book addresses the interplay between the right to free expression (and what that means to a free press) and the right to privacy. Privacy and the criticism that journalists unreasonably and regularly invade it in order to get a 'good story' is the most significant ethical dilemma for journalists, alongside accurately reporting the truth. Where is the line between fair exposure in the public interest and interesting the public? This book explains what privacy is, why we need it and why we go to some lengths to protect it. The law, the regulators, the key court cases, and regulator complaints are covered, as well as issues raised by new technological developments. The book also briefly examines regulators in Ireland as well as privacy and free expression elsewhere in Europe and in North America, considering the contrary cultures of the two continents. This insightful exploration of privacy and journalism combines theory and practice to provide a valuable resource for both Media and Journalism students and working journalists"--